PENGEMBANGAN MEDIA PEMBEJARAN PAPAN PINTAR UNTUK KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS II SDN 05 KOTO BARU - Ahmad Ilham Asmaryadi; Dodi Widiya Nanda; Diana Pungki (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Indonesian is the official language as well as the national language in Indonesia. learning Indonesian is essentially learning to communicate. Smart Board learning media is suitable for use in learning Indonesian and is in accordance with the provisions of SDN 05 Koto Baru. This research aims to determine the beginning reading ability of class II students in elementary school. The types of data in this research are primary and secondary, data collection techniques include observation, interviews and documentation. The results of the research show that the beginning reading abilities of class II students are: Students have difficulty identifying letters, changing words, pronouncing words incorrectly, spelling haltingly, not understanding the content of the reading, and having difficulty concentrating.